Efektivitas Program Pengelolaan Hutan Desa Oleh Lembaga Pengelola Hutan Desa (Studi Kasus: Lembaga Pengelolaan Hutan Desa Medewi, Kecamatan Pekutatan, Kabupaten Jembrana) - Sugiantara, I Putu Oki; Sastra Wijaya, Komang Adi; Putri Wirantari, I Dewa Ayu (CITIZEN CHARTER, 2021)
LPHD Medewi is a village institution in charge of managing village forests in Medewi village. The purpose of this study was to determine the effectiveness of the Village Forest Management Program by the Village Forest Management Institute (Case Study: Medewi Village Forest Management Institute, Pekutatan District, Jembrana Regency). Measurement of effectiveness is carried out through three approaches proposed by Balduck and Buelens, namely the source approach, the process approach, and the goal approach. This study uses descriptive qualitative research methods with data collection techniques in the form of observation, interviews, documentation, and literature study. The results of this study indicate that the village forest management program by LPHD Medewi has been running well but has not been effective because there are still obstacles in the measurement indicators. Keywords: Effectiveness, Village Forest Management Institution, Forest Management Program.